Pelatihan Pembuatan Tepung Mocaf pada Kelompok Wanita Tani di Desa Salenrang Kecamatan Bontoa Kabupaten Maros - Ahmad, Ilham; Ernawati Jassin; Nur Laylah; Imran Muhtar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Salenrang Village, Bontoa District, Maros Regency has quite large potential for cassava commodities, but its utilization is still limited. To increase the added value and independence of local food, training was conducted on making MOCAF (Modified Cassava Flour) flour for the local Women Farmers Group (KWT). The implementation method was in the form of education, demonstration, and direct practice. The results of the activity showed an increase in technical understanding by 80%, as well as the emergence of initiatives for developing household-scale businesses based on mocaf. This activity has proven effective in increasing the capacity, economic role, and entrepreneurial spirit of women in the village.